Genetic Evaluation of A Nation-Wide Dutch Pediatric DCM Cohort: The Use of Genetic Testing in Risk Stratification. (30th September 2022) - van der Meulen, Marijke H.; Herkert, Johanna C.; den Boer, Susanna L.; du Marchie Sarvaas, Gideon J.; Blom, Nico A.; ten Harkel, Arend D.J.; Breur, Hans M.P.J.; Rammeloo, Lukas A.J.; Tanke, Ronald B.; Marcelis, Carlo; van de Laar, Ingrid M.B.H.; Verhagen, Judith M.A.; et al.
Abstract : Background: This study aimed to describe the current practice and results of genetic evaluation in Dutch children with dilated cardiomyopathy and to evaluate genotype-phenotype correlations that may guide prognosis. Methods: We performed a multicenter observational study in children diagnosed with dilated cardiomyopathy, from 2010 to 2017. Results: One hundred forty-four children were included. Initial diagnostic categories were idiopathic dilated cardiomyopathy in 67 children (47%), myocarditis in 23 (16%), neuromuscular in 7 (5%), familial in 18 (13%), inborn error of metabolism in 4 (3%), malformation syndrome in 2 (1%), and "other" in 23 (16%). Median follow-up time was 2.1 years [IQR 1.0–4.3]. Hundred-seven patients (74%) underwent genetic testing. We found a likely pathogenic or pathogenic variant in 38 children (36%), most often in MYH7 (n = 8). In 1 patient initially diagnosed with myocarditis, a pathogenic LMNA variant was found. During the study, 39 patients (27%) reached study endpoint (SE: all-cause death or heart transplantation). Patients with a likely pathogenic or pathogenic variant were more likely to reach SE compared with those without (hazard ratio 2.8; 95% CI 1.3–5.8, P = 0.007), while transplant-free survival was significantly lower ( P = 0.006). Clinical characteristics at diagnosis did not differ between the 2 groups. Conclusions: Genetic testing is a valuable tool for predicting prognosis in children with dilated cardiomyopathy, with carriers of a likely pathogenic or pathogenic variant having a worse prognosis overall. Genetic testing should be incorporated in clinical work-up of all children with dilated cardiomyopathy regardless of presumed disease pathogenesis.